The African Standby Force of the African Union: Ambitious plans, wide regional disparities. An intermediate appraisal - Wolf Kinzel (Stiftung Wissenschaft und Politik (SWP), 2008)
By adopting the joint EU-Africa Strategy, the European Union set course for a comprehensive partnership with the African continent. Peace and security are defined as the primary goals of this strategy. The year 2015 is given as a time horizon. The EU intends to cooperate with the African Union (AU), the sub-regional organizations and individual countries to anticipate conflicts, to prevent them and to act as a mediator in the case of conflict. The question also arises which services the African countries are able to provide within the scope of peace missions. The foundation of the African Union in 2002 and the establishment of the Peace and Security Council (PSC) in March 2004 meant that an adequate security platform had been created for the African countries. A two-phase time schedule was set up envisaging the build-up of an African Standby Force (ASF) suited for peacekeeping operations by 2010. In each of the five regions (North, East, South, West and Central) one brigade each is to be established for peace operations.What does the present AU security architecture look like, and what progress has been made in the individual regions with regard to implementing the set time schedule? Which shortfalls have been identified and where are the key capabilities for peace operations on the African continent? What are the chances for the international community, and with that also for Germany, to contribute to the improvement of the crisis management capabilities?As the build-up of a fully operational African Standby Force will be delayed beyond the target date of 2010, this study will present different approaches to how the international donor community, including Germany, can support the development of the African Union into an efficient crisis management instrument
Keywords: 320